Variability in the Carbon and Nitrogen Uptake Rates of Phytoplankton Associated With Wind Speed and Direction in the Marian Cove, Antarctica - Kim, Bo Kyung; Jeon, Misa; Park, Sang-Jong; Kim, Hyun-Cheol; Min, Jun-Oh; Park, Jisoo; Ha, Sun-Yong (Frontiers in Marine Science, 2022)
Quantifying the temporal variability in phytoplankton productivity is essential for improving our understanding of carbon (C) and nitrogen (N) dynamics and energy flows in natural aquatic ecosystems. Samples were collected at three-day intervals from December 2018 to January 2019 from fixed station in Marian Cove, Antarctica to determine the C and N (NO3- and NH4+) uptake by phytoplankton. Considerable fluctuations in the total C and N productivities were observed, which led to dynamic changes in the phytoplankton communities and a stronger coupling between the phytoplankton biomass. The increased rate of NO3- uptake coincided with an enhanced C uptake mainly by microphytoplankton (>20 µm), followed by an increase in NH4+ uptake towards the end of sampling period. However, the <2 µm fraction (picophytoplankton) showed little variation in C and NO3- uptake, and the proportions of assimilated NH4+ contributed to more than half of the total assimilated inorganic N. The increased NH4+ did not increase the total phytoplankton biomass and C production. Interestingly, after January 9 (maximum chlorophyll a, C, and N uptake) there was a shift to a predominantly easterly wind (>6 m s-1), which rapidly decreased the total chl-a, C and N uptake rate to 4% of the highest values (0.6 mg m-3, 1.0 mg C m-3 h-1, 0.1 mg N m-3 h-1, respectively) on January 12. The phytoplankton community was also replaced by neritic and ice-related species. These findings suggest that strong temporal shifts in phytoplankton C and N assimilation are strongly influenced by external forces (wind stress).